Fusing α and β subunits of the fungal fatty acid synthase leads to improved production of fatty acids - Wernig, Florian; Born, Sandra; Boles, Eckhard; Grininger, Martin; Oreb, Mislav (Scientific reports, 2020)
Most fungal fatty acid synthases assemble from two multidomain subunits, α and β, into a heterododecameric FAS complex. It has been recently shown that the complex assembly occurs in a cotranslational manner and is initiated by an interaction between the termini of α and β subunits. This initial engagement of subunits may be the rate-limiting phase of the assembly and subject to cellular regulation. Therefore, we hypothesized that bypassing this step by genetically fusing the subunits could be beneficial for biotechnological production of fatty acids. To test the concept, we expressed fused FAS subunits engineered for production of octanoic acid in Saccharomyces cerevisiae . Collectively, our data indicate that FAS activity is a limiting factor of fatty acid production and that FAS fusion proteins show a superior performance compared to their split counterparts. This strategy is likely a generalizable approach to optimize the production of fatty acids and derived compounds in microbial chassis organisms.